Bathocuproine:Ag Complex Functionalized Tunneling Junction for Efficient Monolithic Perovskite/TOPCon Silicon Tandem Solar Cell. Issue 12 (26th October 2022) - Ying, Zhiqin; Yang, Xi; Zheng, Jingming; Sun, Jingsong; Xiu, Jingwei; Zhu, Yudong; Wang, Xinlong; Chen, Ying; Li, Xin; Sheng, Jiang; Shou, Chunhui; Zeng, Yuheng; et al.
Abstract : The single‐crystalline silicon solar cell with tunnel oxide passivating poly‐Si contact (TOPCon) has developed into one of the most promising and high‐performance n‐type Si‐based solar cells in their mass production way because of its high conversion efficiency and robustness. Owing to its unique device structure, TOPCon shows superior advantages over amorphous Si‐based heterojunction one (HJT) in developing high‐performance monolithic perovskite/silicon tandem solar cell because TOPCon may have better tolerance than HJT to the particle bombardments and plasma fluorescence irradiations in the sputtering deposition process of transparent conductive oxide (TCO) recombination layer. Herein, bathocuproine (BCP):silver complex is introduced as a buffer recombination contact between TCO and poly‐SiCX, to modulate the tunneling junction between perovskite/TOPCon. Depending on fine film thickness and derived energy level tuning, BCP:Ag buffer layer can effectively prevent the sputter bombardments and passivate the interface of TCO/poly‐SiCX (n)/SiOX contact, as well as enhancing electron transport. As a result, a certified conversion efficiency of 25.84% is achieved in the monolithic perovskite/TOPCon silicon tandem solar cell. This work definitely paves a new and promising way to develop high‐performance monolithic perovskite/c‐Si tandem solar cells. Abstract : A bathocuproine (BCP):silver buffer layer is introduced to modulate the tunneling junction contact for perovksite/TOPCon tandem solar cell. Owing to reduced sputter damages and enhanced carrier transport, the optimized tandem device achieves a champion power conversion efficiency of 25.84% (certified).